TRUSTWORTHINESS OF HOSTS IN ACCOMMODATION SHARING: THE EFFECT OF FACIAL TRAITS AND EXPRESSIONS - DURMUŞ, BERİL; ÇİNKO, MURAT (AKDENIZ UNIV ZIRAAT FAK, 2021)
The purpose of this paper is to reveal the impact of a host's facial traits and expressions on their perceived trustworthiness and preferences among users of accommodation-sharing platforms. The eye movements of 39 participants in the study while responding to the question of how much they would want to stay in each apartment presented on a created platform were recorded using an eye-tracking device in a controlled offline setting. A further online questionnaire was used to collect data about user preferences, to which 226 people responded. The results reveal the human face to be the most significant source of cognizance on accommodation sharing platforms; that hosts with positive profile photos are trusted and preferred more than those with less positive images; and that hosts with high fWHRs are trusted and preferred less than hosts with lower fWHRs. This study introduces a novel and broad approach to the tourism and hospitality field, involving a review and analysis of the relationships of different variables recorded in literature, confirming the universality of facial traits and expressions.
Keywords: perception; trustworthiness; accommodation sharing; facial width height ratio; emotional expressions; hospitality; EVALUATING FACES; TRUST; WIDTH; CONSUMPTION; AGGRESSION; ATTRIBUTES; PERCEPTION; REPUTATION; DOMINANCE; ATTENTION